Complex Dynamical Properties of Some Special Entire Functions (Journal of Mathematical Study, 2023)
Research on the Julia sets of meromorphic functions has been one of the hottopics in complex dynamics. In this paper, we shall investigate the radial distributionof the Julia sets of entire functions which are extremal for some famous inequalities.Our estimates for these particular functions are more accurate than others.
Keywords: Radial distribution; Borel direction; Fatou set; deficient values.